2004
DOI: 10.1140/epjc/s2004-01896-y
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry realization of texture zeros

Abstract: We show that it is possible to enforce texture zeros in arbitrary entries of the fermion mass matrices by means of Abelian symmetries; in this way, many popular mass-matrix textures find a symmetry justification. We propose two alternative methods which allow to place zeros in any number of elements of the mass matrices that one wants. They are applicable simultaneously in the quark and lepton sectors. They are also applicable in Grand Unified Theories. The number of scalar fields required by our methods may b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
254
2
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(258 citation statements)
references
References 31 publications
1
254
2
1
Order By: Relevance
“…As all entries carry different charges (including the trivial), we can arrange the appropriate texture-zero in the (ee) or (µτ ) entry by making the nonzero entries come from the vacuum expectation values of scalars carrying the desired quantum numbers [32]. We give an explicit construction in section 5.…”
Section: Jhep01(2017)068mentioning
confidence: 99%
See 2 more Smart Citations
“…As all entries carry different charges (including the trivial), we can arrange the appropriate texture-zero in the (ee) or (µτ ) entry by making the nonzero entries come from the vacuum expectation values of scalars carrying the desired quantum numbers [32]. We give an explicit construction in section 5.…”
Section: Jhep01(2017)068mentioning
confidence: 99%
“…The absence of appropriate fields will lead to texture-zeros [32]. Let us introduce SM singlet scalars η k ∼ ω k 8 labelled by their Z 8 charges, k ≤ 7.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from being interesting in itself, several scalar triplets naturally occur in models for neutrino masses and lepton mixing based on the type II seesaw mechanism. In particular, it has been shown that in such a scenario a realization of viable neutrino mass matrices with two texture zeros [24][25][26][27][28][29], 1 using symmetry arguments [34], requires two or three scalar triplets [35]. In this paper, we take up the case of two coexisting triplets.…”
Section: Jhep02(2014)060mentioning
confidence: 99%
“…Some methods which may be relevant for application to our model include a horizontal gauge symmetry in the singlet sector [44] and the supersymmetric realisation of a singular Majorana mass matrix of Du and Liu [45]. The method advocated in [46] to generate arbitrary mass matrix texture zeros could also be employed.…”
Section: Discussionmentioning
confidence: 99%